The UCD and the PSD parties: Iberian synergies in a center-right in transition - Sabater Navarro, Gregorio (Historia y Política, 2022)
The collaboration between the center-right of Spain and Portugal during the transitions to democracy acquires its full meaning in the framework of what is called the «ebb flow» of the Iberian Transitions: a period in which the Spanish Transition, turned into a reference of political change for a part of western public opinión from 1977 onwards, when it began to influence the complex post-revolutionary Portuguese reality. The success of the Unión de Centro Democrático and the governments of Adolfo Suárez —which together with the opposition achieved important achievements in the political, economic and social spheres— became a benchmark for a Portuguese PSD, which was in a process of ideological relocation and fight for power. Therefore, the synergies established with the UCD constituted the main external support of the Aliança Democrática coalition, which led to the arrival of the right to the government of Portugal for the first time after the return of democracy.
Keywords: Democratization; Iberian Transition; political parties; center-right; Portugal